2006
DOI: 10.1637/7640-050106r.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pathogenic Characterization of H6N1 Avian Influenza Viruses Isolated in Taiwan Between 1972 and 2005

Abstract: This article reports the genetic and pathogenic characteristics of 34 isolates of H6N1 avian influenza viruses isolated in Taiwan between 1972 and 2005. Genetic analyses showed that a unique lineage of H6N1 viruses has been established in domestic chickens in Taiwan since 1997, and this lineage of viruses differs from the H6N1 viruses circulating in Hong Kong and Southeastern China. Pathogenicity tests showed that all Taiwanese H6N1 viruses were of low pathogenicity but might lead to economic loss when associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 24 publications
2
61
0
Order By: Relevance
“…All but five of the over 100 H6 viruses isolated and sequenced in this period from chickens and other terrestrial poultry were W312-like (4). Interspecies transmission and subsequent establishment of H6 viruses in terrestrial poultry occurred in southern China (4), Taiwan (10), and California (16,18) before. Phylogenetic analyses demonstrated that the HA genes of these viruses were of aquatic avian sources and are of lineages different from the lineages of the duck viruses isolated here.…”
Section: Figmentioning
confidence: 99%
“…All but five of the over 100 H6 viruses isolated and sequenced in this period from chickens and other terrestrial poultry were W312-like (4). Interspecies transmission and subsequent establishment of H6 viruses in terrestrial poultry occurred in southern China (4), Taiwan (10), and California (16,18) before. Phylogenetic analyses demonstrated that the HA genes of these viruses were of aquatic avian sources and are of lineages different from the lineages of the duck viruses isolated here.…”
Section: Figmentioning
confidence: 99%
“…Although this A(H6N1) (A/Taiwan/2/2013) infection was the first reported human case, the A(H6N1) subtype avian influenza virus has been circulating throughout North America and Eurasia for many years (18,19). Indeed, H6-specific antibodies have previously been detected in personnel working in Chinese live-animal markets as well as U.S. veterinarians exposed to birds (20,21).…”
mentioning
confidence: 96%
“…Furthermore, two of 11 healthy human volunteers inoculated with the H6N1 virus displayed mild upper respiratory symptoms, suggesting that this virus has the potential to infect mammals (Beare and Webster, 1991). In addition, some Taiwanese H6N1 viruses can replicate in mice without pre-adaptation (Lee et al, 2006). Therefore, clinically asymptomatic or unreported human infections of H6 viruses may have occurred.…”
Section: Co-circulating H5n2 Infl Uenza Viruses Reassorted With H6n1 mentioning
confidence: 99%
“…Avian infl uenza A (H6N1) virus has been circulating throughout North America (Senne, 2003) and Eurasia (Lee et al, 2006) for many years. In Taiwan, the H6N1 virus has been circulating for over 30 years and is extremely prevalent among poultry, with approximately half of the layers and 30% of the broilers having antibodies against H6N1 influenza viruses ( Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation